Prioritising national dementia guidelines for general practice: A Delphi approach. (10th November 2021) - Mazza, Danielle; McCarthy, Edwina; Camões‐Costa, Vera; Mansfield, Elise; Bryant, Jamie; Waller, Amy; Lin, Xiaoping; Piterman, Leon
Abstract: Objectives: Australian guidelines for dementia cover 109 recommendations for dementia care. Knowing which recommendations to implement poses a challenge for general practitioners (GPs). This study aimed to gather general practice perspectives of priority recommendations for GPs in their practice. Methods: To explore which recommendations are most important and those requiring the greatest support in GP implementation, a Delphi study was conducted. Thirty‐six GPs, 4 practice nurses and 1 medical services director completed two rounds of email questionnaires. Results: Recommendations requiring support for GP implementation relate to early assessment of behavioural and psychological symptoms; mental health interventions tailored to the person's preferences and abilities; language and cultural barriers in access to information and services; and cognitive and learning needs in treatment delivery. Conclusions: It is critical to understand where support may be needed for GPs to successfully implement recommendations to improve care provided to people with dementia and their carers.